A Study on Paradiguna (Samskara) W.S.R to “Samaskarohi Gunantaradhanam Uchyate” and ITS Applied Aspect in the Management of Mukhadushika with an Indiginous Drug - Biswas, Susmita; Sahoo, Manoj Kumar (International Research Journal of Ayurveda & Yoga, 2024)
Introduction: Acharya Charaka has clearly said that if one does not understand these Paradi Guna in proper way then he cannot perform Chikitsa in desire manner. Paradi Gunas are the one in which a physician needs to be expertise. Paradigunas are necessary in the field of pharmaceutical science, as well as by the physicians to treat the patients and researchers conducting research and creating new formulation. Samskara Guna is one of the important factors in the hands of Ayurvedic physician for improving other third padas of Bhesaja (i.e., Bahuta, Yogyatwa, and Sampat). Thus in this study, an attempt was made to know the comparative effect of Manjistha Lepa and Samskrita Manjistha with Madhu Lepa in the management of Mukhadushika. Aims and Objectives: The aim of the study was to study about the comparative clinical efficacy of Manjistha Lepa and triturated with Madhu Lepa in the management of Mukhadushika. Materials and Methods: This is a single-blind comparative clinical study with a pre-test and post-test design. The patients were randomly categorized into two groups. Forty patients of Group A (20) and Group B (20) patients were registered from outpatient department of Government Ayurvedic College and Hospital, Balangir, and Saradeswari Government Hospital, Balangir, presented with subjective parameters and objective parameters. After diagnosis, they were under trial with Ayurvedic formulations of Manjistha Lepa for local application and Manjistha triturated Madhu Lepa given 05 g in morning time daily, after drying face wash with normal water for 15 days, respectively. The subjective and objective parameters were assessed in 7-day interval to interpret the result by statistical evaluation. Observation and Results: It had been observed that the result of trial drug Group B patients was significant (<0.05) to reduce both subjective and objective parameters after 15 days of treatment as compared to Group A patients. In Group A, NO patients had marked improvement, while 15% of patients had moderate improvement, 65% mildly improved and 20% had shown unsatisfactory result. In Group B, no patients had marked improvement, 50% moderate, 40% mildly improved, and 10% of patients showed unsatisfactory results. In both groups, the result was statistically significant, but more improvement was noticed in Group B. Conclusion: On comparison between two groups, Manjistha triturated with Madhu Lepa in Group B had shown more effect than Manjistha Lepa in Group A. No adverse effects were noticed during clinical trial in both groups.